Planning and Design of Hotel Resort in Karang Aji Beach Area, Serasan District, Natuna Regency with a Vernacular Architecture Approach - tio syahada; Eka Widyaningsih (Yayasan Putra Adi Dharma, 2024)
Natuna Regency is one of the regions in Riau Islands Province, Indonesia, Natuna Regency is one of the districts that is a priority scale of development by President Joko Widodo, there are 5 sectors of accelerated development in Natuna Regency, including the tourism sector. The strategic location is also a great potential in the field of tourism, as a district bordering 2 countries, namely Singapore and Malaysia, the construction of this hotel resort will increase and develop tourism potential in the Natuna Regency area. In addition, the choice of Karang Aji Beach as the location for the design was because the beach symbolized identity as one of the Indonesian territories where in the background of Karang Aji Beach was once a feud between two countries, namely Singapore and Indonesia, where Singapore at that time recognized the beach as its own because it had purchased land in the coastal area. As one of the regions that will develop tourism potential, the main problem faced is the lack of quantity and quality of tourism facilities and infrastructure. The lack of resort-based hotel lodging accommodation in Natuna regency is one of the problems faced in the development of tourism areas.